Algunos planteamientos teóricos frente a los programas de transferencias condicionadas y el derecho a la alimentación (2018)
ABSTRACT: To propose a conceptual and theoretical reference framework for the analysis of the CCTP and its role in relation to the right to food. Materials and methods: This article is a theoretical research derived from a framework study, which was based on the grounded theory method and whose purpose was to understand the meaning of food policies for a group of beneficiaries. Results: The right to food has a political and economic context that corresponds to a neoliberal state, which focuses its social policy on the fight against poverty, although only in some of its expressions. Poverty is conceived as a deficit of human capital and the conditioned cash transfer programs constitute the emblematic strategy of the social policy in neoliberalism. In this scene, of conditioned cash transfer programs become mechanisms for the inclusion of the poor people in the market, where the subjects must procure their food. Analyzes derived from the framework research allow understanding that the cash transfer programs do not solve the food security situation of the beneficiaries. Conclusion: The conditioned cash transfer programs, as part of a residual social assistance approach, do not guarantee the right to food but rather head the poor people towards procuring themselves their food, under conditions of clear disadvantage compared to the rest of the population.